Volume ratios of painted chromosome territories 5, 7 and X in female human cell nuclei studied with confocal laser microscopy and the Cavalieri estimator - Rinke, Bernd; Bischoff, Axel; Meffert, Marie-Christine; Scharschmidt, Rainer; Hausmann, Michael; Stelzer, Ernst H. K.; Cremer, Thomas; Cremer, Christoph (Bioimaging, 1995)
Chromosome territories 5, 7 and X were painted in female human amniotic fluid or fibroblast cell nuclei with chromosome specific DNA library probes. For probe detection the fluorochromes FITC or TRITC were applied. Using confocal laser scanning fluorescence microscopy ten to twenty light optical sections of FITC or TRITC images were registered with equal spacing (approximately 400 nm) for each of 131 nuclei showing well separated homologous chromosome territories. Chromosome territory areas were segmented applying a range of gray value thresholds to each section. For each gray value threshold the territory volumes for a given pair of homologs were computed by means of the Cavalieri estimator. The larger volume was divided by the smaller one to obtain a volume ratio. Between 9 and 26 territory volume ratios were calculated for a pair of homologs in a given nucleus. This approach yielded the following results: (i) the range of volume ratios was very similar for both autosome and X-chromosome territories and (ii) most volume ratios (> 70%) were between 1 and 1.5. The same results were obtained for cells fixed with 4% buffered formaldehyde or methanol/acetic acid indicating that volume ratio measurements are relatively robust against shrinkage effects induced by the latter type of fixation. These similarities of volume ratios argue against the view that the genetic inactivation of one X-chromosome territory in female cell nuclei should be correlated with a decrease of its volume. Such a decrease was expected in case of a strong overall condensation of this chromosome as compared to other chromosomes.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2001
Gesehen am 06.08.2024